Pojęcie „obszaru oddziaływania obiektu” w Prawie budowlanym po nowelizacji z dnia 13 lutego 2020 roku - Kosicki, Artur (PRAWO i WIĘŹ, 2025)
As it results from the content of art. 5 sec. 1 point 9 of the Act of 7 July 1994 – Building Law, the main determinant of the possibility of using public law instruments to protect the interests of third parties in the construction process is the area of ​​impact of the facility, referred to in art. 3 point 20 of this act. The provision of art. 5 sec. 1 point 9 of the Building Law directly refers to respecting the legitimate interests of third parties present in this area. The Act of 13 February 2020 amending the Building Law and certain other acts introduced new wording to the definition of the area of impact of the facility. This should be understood as the area designated in the surroundings of the building on the basis of separate provisions introducing restrictions on development in this area related to the facility in question. Prior to the aforementioned amendment, however, this area was understood as the area designated in the surroundings of the building on the basis of separate provisions introducing restrictions on development related to this facility, including development of this area. This paper aims to demonstrate the essence of the change introduced by the amendment and examine its impact on the protection of third-party interests in the construction process. This will be achieved by taking into account case law from administrative courts and the views of legal scholars on the basis of the previously applicable and current definitions.